The Effect Of Discovery Learning Toward Reading Comprehension Of The grade Eight Students At SMP Labschool UNTAD Palu - Dela Zahra; Mashuri Mashuri; Sriati Usman (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The Effect of Discovery Learning on the Reading Comprehension Skills of Eighth-Grade Students at SMP Labschool UNTAD Palu. This study aims to examine the effect of the Discovery Learning model on the reading comprehension skills of eighth-grade students at SMP Labschool UNTAD Palu. A quasi-experimental design with a pretest-posttest control group was employed, involving two groups: an experimental group taught using Discovery Learning and a control group taught with conventional methods. The sample consisted of 36 students selected through purposive sampling.The results revealed that the experimental group showed a significant improvement in post-test scores, with an average of 76.00 compared to their pretest average of 59.00. In contrast, the control group exhibited only a slight increase from 50.18 to 60.00. Statistical analysis using an independent t-test confirmed a significant difference between the two groups (p < 0.05), indicating that Discovery Learning effectively enhances students' reading comprehension.